Freehand text entry in virtual reality - Liu, Zijia (2017)
With the growth of requirements and applications in Virtual Reality (VR), text entry for current VR is not as satisfying as that on other platforms such as PC or mobile phones. This paper focuses on creating a freehand mid-air text input method for VR, which requires no physical devices in contact with hands. In this paper, we started with an extensive review of current solutions to this issue. Then we developed a freehand text input method, whose entire process is introduced in the main content including information gathering, requirement establishing, design, implementation, and testing. To the author’s knowledge, this is the first freehand text entry implemented for VR applications. Finally, based on the experience gained in this project, several design suggestions are proposed for future study and development in the same area.